2000
DOI: 10.1001/archotol.126.3.371
|View full text |Cite
|
Sign up to set email alerts
|

Swallowing Function in Patients With Head and Neck Cancer Prior to Treatment

Abstract: Hypopharyngeal and laryngeal disease sites have a high degree of pretreatment functional impairment. The SPSS score is a good global measure of swallowing dysfunction. In addition, significant site-specific dysfunctions are found when the OPM study is analyzed via its separate parameters. It is therefore critical that posttreatment function is compared with baseline pretreatment dysfunction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
99
3
2

Year Published

2000
2000
2020
2020

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 147 publications
(109 citation statements)
references
References 22 publications
5
99
3
2
Order By: Relevance
“…3,4,20 Nevertheless, from retrospective reviews, it appears that the long-term rate of feeding tube requirement is similar, 17,19 with the notable exception of the study by Fein et al, 14 who reported on 490 patients treated with radiotherapy alone for oropharyngeal primary tumors and noted permanent gastrostomy tubes in only two patients. In our cohort, similar to reports by other groups, [24][25][26] patients with hypopharyngeal and laryngeal primary tumors were at greatest risk for swallowing dysfunction after CRT. These patients may benefit from intensive swallowing and physical therapy before, during, and after treatment.…”
Section: Discussionsupporting
confidence: 90%
“…3,4,20 Nevertheless, from retrospective reviews, it appears that the long-term rate of feeding tube requirement is similar, 17,19 with the notable exception of the study by Fein et al, 14 who reported on 490 patients treated with radiotherapy alone for oropharyngeal primary tumors and noted permanent gastrostomy tubes in only two patients. In our cohort, similar to reports by other groups, [24][25][26] patients with hypopharyngeal and laryngeal primary tumors were at greatest risk for swallowing dysfunction after CRT. These patients may benefit from intensive swallowing and physical therapy before, during, and after treatment.…”
Section: Discussionsupporting
confidence: 90%
“…In addition, symptomatic or asymptomatic aspiration may be present. 41 The degree of impairment depends on the anatomic location of the tumor. Laryngeal and hypopharyngeal carcinomas are severely affected compared with other sites.…”
Section: Combined Therapy For Head and Neck Malignancies/nguyen Et Almentioning
confidence: 99%
“…In present study majority (34.89 %) of patients with aspiration had laryngeal cancer followed by tongue cancer (22.14 %). In contrast, Stenson et al [12] reported that the incidence rate of aspiration reaches 30, 67, and 80 % in patients with oral, laryngeal, and pharyngeal head and neck cancers respectively, whereas Starmer et al [13] reported that head and neck cancer involving the larynx or the hypopharynx is a principal risk factor for aspiration. Eischbruch et al [1] reported that though swallowing-related structures were normal, radio therapy and chemotherapy affects movement of the oral cavity and laryngopharyngeal musculature and, thus, causes aspiration.…”
Section: Discussionmentioning
confidence: 95%
“…The destruction of normal tissues by head-and-neck malignancies, surgery, inflammation, and/or radiation-induced fibrosis of the pharyngeal muscles are potential mechanisms responsible for dysphagia in head-and-neck cancer patients [8]. When aspiration occurs because of compromise of the swallowing reflex, pneumonia and respiratory failure may lead to death [1].…”
Section: Discussionmentioning
confidence: 99%